Coping-strategies of Behavior in Teenagers: the Practical Dimension. (Journal of Educational Sciences, 2016)
As the relevance of the chosen theme of the article, the authors show the importance of controlling behavior or psychological overcome the difficulties of life, so necessary to modern man. In the main part of the article the authors present the results of a mini-survey conducted among the students of grade 9 school gymnasium №118. To identify the predominant coping strategies of adolescent behaviors were used: research methodologybasic coping strategies Indicator strategies of coping with stress»(J.Amirkhan) and methods of psychological diagnostics coping mechanisms (E. Heim). Also in the interim mini-study was approved program of productive coping strategies, the aim of which was the formation of arbitrary regulation of the behavior of adolescents, by influencing the mechanisms of consciousness, the development of volitional stability, concentration, self-regulation, arbitrary maturity, self-management skills. Before and after the tests required were the methods of psychological diagnostics coping mechanisms of E. Heim (intermediate and control section).
Keywords: suicidal behavior; could use behavior; coping; coping strategies; coping behavior; copy mechanisms; volitional regulation; selfregulation